Training on Making Modified Formula Food Made from Green Beans and Anchovies: Stunting Prevention Strategy - Pasaribu, Rina Doriana; Nasution, Erlina; Marthoni, Oslida (Newinera Publisher, 2025)
The main cause of stunting is the lack of nutritional intake since the golden period of the first life of toddler growth. Education through counseling, demonstration, and practice is very good and necessary because it has a very important role in the implementation of integrated health posts, with increased nutritional knowledge that will affect the PMT provided, and socialization delivered to mothers of toddlers. This study aims to analyze the effect of training on modified food formula made from green beans and anchovies on knowledge and attitudes. This study is a quasi-experimental research. The target of the training was 30 consisting of health cadres, PKK mothers, and mothers who have babies/toddlers at risk of stunting. The training was conducted for 2 days. Data were collected using a questionnaire and analyzed using a paired t-test. The results showed a significant change in the average knowledge and attitudes of training participants (p-value <0.05). This finding provides a new understanding of efforts to prevent stunting.